Cholesterol-Lowering Drugs and Incident Open-Angle Glaucoma: A Population-Based Cohort Study - Marcus, Michael W.; Müskens, Rogier P. H. M.; Ramdas, Wishal D.; Wolfs, Roger C. W.; De Jong, Paulus T. V. M.; Vingerling, Johannes R.; Hofman, Albert; Stricker, Bruno H.; Jansonius, Nomdo M. (PLOS ONE, 2012)
Background Open-angle glaucoma (OAG) is a progressive neurodegenerative disease that may lead to blindness. An elevated intraocular pressure (IOP) is its major risk factor. OAG treatment is currently exclusively directed towards the lowering of the IOP. IOP lowering does not prevent disease progression in all patients and thus other treatment modalities are needed. Earlier studies reported cholesterol-lowering drugs to have neuroprotective properties. The aim of this study was to determine the associations between the use of cholesterol-lowering drugs and incident OAG. Methodology/Principal Findings Participants in a prospective population-based cohort study underwent ophthalmic examinations, including IOP measurements and perimetry, at baseline and follow-up. The use of statins and non-statin cholesterol-lowering drugs was monitored continuously during the study. Associations between the use of cholesterol-lowering drugs and incident OAG were analyzed with Cox regression; associations between cholesterol-lowering drugs and IOP at follow-up were analyzed with multiple linear regression. During a mean follow-up of 9.8 years, 108 of 3939 eligible participants (2.7%) developed OAG. The hazard ratio for statin use was 0.54 (95% confidence interval 0.31–0.96; P = 0.034) and for non-statin cholesterol-lowering drugs 2.07 (0.81–5.33; P = 0.13). The effect of statins was more pronounced with prolonged use (hazard ratio 0.89 [0.41–1.94; P = 0.77] for use two years or less; 0.46 [0.23–0.94; P = 0.033] for use more than two years; P-value for trend 0.10). The analyzes were adjusted for age and gender, baseline IOP and IOP-lowering treatment, the family history of glaucoma, and myopia. There was no effect of statins on the IOP. Conclusions/Significance Long-term use of statins appears to be associated with a reduced risk of OAG. The observed effect was independent of the IOP. These findings are in line with the idea that statins have neuroprotective properties and may open a way to a new OAG treatment modality.